Scrutinizing Non-English Major Students’ Perceptions of Informal Digital Learning of English - Sujarwati, Iis; Aydawati, Emilia Ninik (Universitas Hamzanwadi, 2025)
The educational landscape has undergone a profound transformation with the rise of Informal Digital Learning of English (IDLE), reshaping language acquisition beyond traditional classroom settings. Although many studies have explored IDLE, research has primarily focused on English majors or highly motivated language learners, leaving a gap in understanding how non-English major students, who have varying levels of motivation and language exposure, engage with IDLE. This study investigates the perspectives of non-English major students on IDLE and its perceived effectiveness in their language learning journey. A total of 169 students from the nursing and accounting disciplines at the University of Bengkulu enrolled in a general English course and participated in the study. Data were collected through structured surveys and semi-structured interviews, with analysis conducted using both statistical and thematic approaches. The findings reveal that participants strongly agree that IDLE provides language support (M = 4.55), flexibility in use (M = 4.25), and contributes to increasing their language proficiency (M = 4.58). However, challenges such as the lack of structured feedback and inconsistent learning patterns were also noted. These insights underscore the potential of IDLE as a valuable supplement to formal instruction. Educators are encouraged to integrate IDLE into curricula through engaging, personalized digital learning strategies catering to non-English major students' distinct needs. Future research should explore the long-term impact of IDLE on language proficiency and best practices for its implementation.